Figure poses for fashion illustrators - Tahmasebi, Sha (Hauppauge, N. Y Barron's, 2011)
"Drawing a correctly proportioned figure is the foundation of fashion illustration. The most detailed and accurate drawing cannot convey a garment's true appearance unless it shows a properly drawn figure wearing it...Packed with scores of correctly proportioned fashion poses, suitable for a variety of garments and styles, this book shows design students how to draw and render the draped figure perfectly, every time..."--P. [4] of cover
"Includes a CD-ROM with over 250 copyright-free images."
"Scan, trace, copy : 250 templates for professional results"--Cover
Includes index
1 13
Keywords: Fashion drawing